Phytochemical and cytotoxicity evaluation of lagerstroemia speciosa (L.) leaves extract by MCF-7 cell line and brine shrimp lethality bioassay - Azad, Abul Kalam; Helal Uddin, A.B.M. (International Journal of Drug Delivery Technology, 2020)
This study aimed to investigate the cytotoxicity of Lagerstroemia speciosa (L.) leaves crude extract. It has been reported to show various bioactivities. The phytochemical screening of the extract has been carried qualitatively. The cytotoxic effect was determined through in vitro MTT assay of MCF-7 cell line, and brine shrimp lethality bioassay. The presence or absence of alkaloid, carbohydrate, glycoside, saponin, terpene, steroid, phenol, and flavonoid in the extract was determined through the qualitative tests. The extract showed cell viability of 100% (1.95–3.9 μL/mL), 96% (1.95 μL/mL), ≈ 95% (3.9–15.62 μL/ mL) and 88% (250 μL/mL) while the mortality of brine shrimp nauplii was from 5% to 10% (7.8 – 125 μL/mL) respectively. For both assays, DMSO of 1 & 0.1% were used as vehicle controls, while the potassium dichromate as the positive control for the brine shrimp only. These results proved the leaves extract to be non-toxic.